Poster 141: Novel Equation to Accurately Compute the Glenoid Bone Loss with a Bony Bankart. Issue 7 (30th July 2022) - Nelson, Ralph; Marwan, Yousef; Paruthikunnan, Samir; Laverdiere, Carl; Martineau, Paul; Boily, mathieu; Bozzo, Isabella
Objectives: The glenohumeral joint is the most frequently injured joint, with anterior dislocations occurring in 98% of cases. There is often an osseous Bankart fragment (OBF) of the glenoid rim that remains in both acute and chronic instability. By calculating the percent bone loss (%BL) of the glenoid surface, the best reconstruction method is selected. Reported values of the critical %BL range from 13.5 to 25%. This study validates a new geometric equation to compute the glenoid %BL for patients undergoing shoulder stabilization surgery and accounting for the decrease in bone loss expected with incorporation of the OBF into the anticipated repair. The goal of the study was to determine if the accuracy of the %BL computed with the novel equation would improve compared to the diameter ratio, as well as if the inclusion of the OBF would indicate a pre-operative selection of more conservative reconstructive management. Methods: This retrospective radiographical validation study reviewed pre-operative CT scans for 36 patients who underwent surgical reconstruction for shoulder dislocations with Bankart lesions, with and without OBFs. Two independent raters measured the dimensions required for the novel equation, the diameter ratio, and the 'true' area from pre-operative CT scans three months apart. The %BL for these three methods and the reduction in %BL by including the OBF were compared. As well, the validity of the measurement technique was assessed through inter-and intra-rater analyses. Results: Our findings revealed the novel equation was more accurate in determining the %BL versus the diameter ratio. Without the OBF, the %BL was most similar for the novel equation (23.514% ± 13.613%) and area method (21.223% ± 9.842%), and there was no statistically significant difference between the %BL for these two methods (p-value = 0.423). Instead, the diameter ratio had larger values of %BL (27.774% ± 12.00%) and there was a statistically significant difference compared to the %BL obtained with the area method (p-value = 0.015). Furthermore, by including the OBF in the reconstruction this would have led to a change in pre-operative surgical plan for 50% of patients, favouring more conservative repairs since the %BL would have been below the selected critical cut-off value of 13.5%. Conclusions: By accounting for the area overestimate of the diameter ratio and incorporating the OBF, our novel equation reduced the %BL in general, even below the critical threshold for half of our cohort. Future studies will investigate the clinical implications of our novel equation, and its impact in pre-operative planning through large scale randomized-controlled trials with long term post-operative functional outcomes assessment. This research paves the way for potentially less invasive treatment options, and improvement in post-repair outcomes, such as greater long-term shoulder stability, decreased incidence of re-tearing and faster recovery time.